Expression evaluation of exogenous and endogenous alcohol dehydrogenase genes in transgenic Arabidopsis - Yu, Haoqiang; Lv, Hong; Lu, Fengzhong; Yang, Qingqing; Duan, Huaming; Li, Wanchen; Fu, Fengling (Frontiers in Plant Science, 2025)
A lot of endogenous genes, as well as genes from related species, are transformed back into crops for overexpression to improve their corresponding traits. However, almost all of these transgenic events remain at the testing stage. Most of the singular transgenic events of crops approved for commercial release are developed by the transformation and heterologous expression of exogenous genes from distant species. To detect the differences in expression, protein accumulation, and enzyme activity between transformed exogenous and endogenous genes, the coding sequences (CDSs) of the alcohol dehydrogenase (ADH) genes were cloned from dicotyledonous Arabidopsis, monocotyledonous maize, and prokaryotic Escherichia coli, constructed into expression vector pBI121-cMycNY, and used to transform wild-type Arabidopsis, respectively. Three homozygous T3 lines with a single integration site were screened for each of the three transformed genes by antibiotic screening, polymerase chain reaction (PCR) identification, and genomic DNA resequencing. Real-time quantitative PCR (RT-qPCR) analysis showed that the relative expression levels of the transformed exogenous ZmADH and EcADH genes were ten or tens of times higher than that of the transformed endogenous AtADH gene. After confirming the encoded proteins of these transformed genes by Western blotting, enzyme-linked immunosorbent assay (ELISA) showed that the accumulation levels of the proteins encoded by the transformed genes ZmADH and EcADH were significantly higher than that encoded by the transformed endogenous gene AtADH. Enzyme reaction assay showed that the ADH activities of the T3 lines transformed by the exogenous genes ZmADH and EcADH were also significantly higher than that transformed by the endogenous gene AtADH as well as the wild-type control. These results indicated that exogenous genes were more conducive to transgenic improvement of crops.